The big carrot: high stake incentives revisited - Pablo Bra\~nas-Garza; Teresa García-Mu\~noz; Shoshana Neuman (Institute for the Study of Labor (IZA), 2008)
This paper provides an empirical demonstration of high stakes incentives in relation to religious practice. It shows that, when both positive (carrot) and negative (stick) incentives are available, the former are more effective than the latter. Specifically, it is shown that beliefs in heaven are much more relevant than beliefs in hell when estimating the production of religious commodities (church-attendance and praying equations).
Keywords: C91; 330; Carrot/stick; high stakes; rewards; punishment; economics of religion; Religion; Anreizregulierung; Verhaltensökonomik; Kirchenpolitik